Contribution of the laboratory to a diagnosis process by sequential reflective testing: Paraprotein interference on a direct bilirubin assay - Yilmaz, Niyazi Samet (Array, 2021)
Errors in laboratory medicine occur in the preanalytical, analytical, and postanalytical phases. The errors are mostly detected in the preanalytical period. However, analytical errors are still an important source of error, despite their frequency is reduced significantly in years thanks to developments in laboratories. In this case, an analytical error was noticed during the verification of a patient"s results. The direct bilirubin of a 66-year-old male patient admitted to the emergency department was higher than the total bilirubin. The patient"s symptoms were fatigue and dyspnoea. Albumin and haemoglobin (Hb) concentrations of the patient were significantly low. After considering the patient"s demographics and laboratory results, the laboratory specialist suspected a paraproteinemia interference. Total protein was performed as a reflective test. The albumin/globulin ratio was reversed. Thereafter, serum protein electrophoresis (SPEP) and immunofixation electrophoresis (IFE) were performed as another reflective tests, respectively. SPEP and IFE results were in favour of monoclonal gammopathy. The patient was directed to a haematologist, underwent a bone marrow biopsy, and the result was reported as Waldenstrom"s macroglobulinemia with plasma cell differentiation expressing IgM-Kappa. The patient went on a chemotherapy protocol, and his condition has been improved in subsequent months. Detection of analytical errors is of great importance, like in our case, and may be used as a tool to identify patients who have not yet been diagnosed. The laboratory specialist must dominate the entire process of each test in the laboratory, be aware of the limitations of tests, and turn these disadvantages into advantages when necessary.